1996
DOI: 10.1063/1.118031
|View full text |Cite
|
Sign up to set email alerts
|

Observation of large low-field magnetoresistance in trilayer perpendicular transport devices made using doped manganate perovskites

Abstract: We report on the fabrication of a new class of trilayer epitaxial thin film devices based on the doped perovskite manganates La–Ca–Mn–O and La–Sr–Mn–O. We show that large resistance changes, up to a factor of 2, can be induced by a moderate applied magnetic field below 200 Oe in these trilayers supporting current-perpendicular-to-plane transport. These results show that low-field spin-dependent transport in manganates can be accomplished, the magnitude of which is suitable for magnetoresistive field sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
165
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(178 citation statements)
references
References 0 publications
5
165
1
Order By: Relevance
“…Detailed analysis of the transport properties of correlated heterostructures including current-voltage characteristics is directly relevant to device applications. 10,11,12,13 However, this area remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of the transport properties of correlated heterostructures including current-voltage characteristics is directly relevant to device applications. 10,11,12,13 However, this area remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite manganite La 0.67 Sr 0.33 MnO 3 (LSMO) is widely used in spintronics, because of its half metallicity and high T C of 370 K [11][12][13][14]. This has resulted in magnetic tunnel junctions with exceptionally large tunnel magnetoresistance ratio [13].…”
mentioning
confidence: 99%
“…[1][2][3] In such a tunnel junction, the junction magnetoresistance ͑JMR͒ is determined by the difference in the density of states for tunneling. Highly spin-polarized magnetic oxides, halfmetallic oxides, are expected to exhibit large, almost infinite JMR in the Julliere model.…”
mentioning
confidence: 99%
“…4 In reality, it has been shown that there is a strong temperature dependence of the JMR in the doped manganite system, i.e., premature loss below the Curie temperature. 1 This result is important for technological applications and depends on the quality of the junctions: uniformity and quality of barrier layer, interface sharpness, and surface magnetization. For the study of its physical origin, the sharp interface and defect-free barrier layer in the trilayered tunnel junction are required and must be controlled on an atomic scale.…”
mentioning
confidence: 99%